Successful management of a difficult airway in a case of advanced thyroid cancer - Ambreen Abdullah Unar; Faisal Shamim; Deewani, Muhammad Hammad; Muhammad Wasif; Mubasher Ikram (Journal of the Pakistan Medical Association, 2023)
Papillary thyroid carcinoma is the most prevalent endocrine malignancy of the head and neck region. It makes up to 80% of all thyroid cancers, and has a 10-year survival rate of up to 95%. Differentiated thyroid carcinomas have good prognosis after a complete surgical extirpation as long as it is not associated with invasion of the surrounding structures. The advanced papillary thyroid carcinoma can invade the neighbouring structures of the thyroid gland, such as strap muscles, recurrent laryngeal nerve, trachea, oesophagus, larynx, pharynx, and carotids. Whenever papillary thyroid carcinoma is associated with invasion of aerodigestive tract it is difficult to excise the tumour. We report a patient with stage IV invasive papillary thyroid carcinomas as per Shin Staging system. The surgery was deferred from several hospitals considering the advanced stage of the disease with tracheal extension making it a problematic airway for both the anaesthesiologist and the operating surgeon. —Continue